University Community Engagement and the Strategic Planning Process - Newton Miller, Laura (Evidence Based Library and Information Practice, 2018)
Objectives – To understand how university libraries are engaging with the university community (students, faculty, campus partners, and administration) when working through the strategic planning process. Methods – Literature review and exploratory open-ended survey to members of CAUL (Council of Australian University Librarians), CARL (Canadian Association of Research Libraries), CONZUL (Council of New Zealand University Librarians), and RLUK (Research Libraries UK) who are most directly involved in the strategic planning process at their library. Results – Out of a potential 113 participants from 4 countries, 31 people (27%) replied to the survey. Libraries most often mentioned the use of regularly-scheduled surveys to inform their strategic planning, which helps to truncate the process for some respondents, as opposed to conducting user feedback specifically for the strategic planning process. Other quantitative methods include customer intelligence and library-produced data. Qualitative methods include the use of focus groups, interviews, and user experience/design techniques to help inform the strategic plan. The focus of questions to users tended to fall towards user-focused (with or without library lens), library-focused, trends and vision, and feedback on plan. Conclusions – Combining both quantitative and qualitative methods can help give a fuller picture for librarians working on a strategic plan. Having the university community join the conversation on how the library moves forward is an important but difficult endeavour. Regardless, the university library needs to be adaptive to the rapidly changing environment around it. Having a sense of how other libraries engage with the university community benefits others who are tasked with strategic planning.